Demographic Risks of the Pension Reform in the Russian Federation - Solovyev, Arkady Konstantinovich (Economy of Regions, 2016)
The purpose of the study is to analyze the impact of the demographic crisis in the country's fiscal system. In the article, the pension system for the first time is considered as a multifactorial model, which during the different historical periods corrects the degree of its dependence on the interdependent complex of macroeconomic and demographic factors. The economically sound and socially correct accounting of the interference of retirement age and the specified development factors of pension system requires a fundamental change in the methodological approaches to the problem of raising the retirement age by using the actuarial methods of forecasting. Ibe actuarial analysis of the problem of retirement age shows that the perception of the linear dependence on demographic parameters of the age when the national pension is awarded cannot be considered as a tool for regulating the efficiency of the pension system. For the science-based solution to the problem of rising the retirement age, along with the dynamics of demographic parameters, it is necessary to take into account the whole range of macroeconomic conditions for the state development as well as the long-term socio-economic consequences. Another significant result of the study are the specific parameters of the actuarial assessments of the impact of demographic and macroeconomic conditions of increasing the retirement age in Russia, conducted using the state statistical data. The practical proposals to mitigate the negative economic consequences are formulated. Ibe key conclusion reached is that the raising of the retirement age should be aimed exclusively at the economic stimulation of the formation of the pension rights of the insured in the long term, rather than to the short-term savings of the state budget. The methodological approaches grounded in the work, and the quantitative results of the actuarial calculations may be applied in the shaping the public pension policy when preparing the regulations for raising the retirement age, the pension formula for calculating the pension rights of the insured, the mechanism of pension indexation.